Guidance manual for the minimisation of NDMA and other nitrosamines in drinking and recycled water - Newcombe, Gayle; Culbert, Julie; Morran, Jim (IWA Publishing, 2013)
N-nitrosodimethylamine (NDMA) is a nitrogen-containing organic compound that has known carcinogenic properties. NDMA has been a health concern for some industries for a number of years as it is used in rubber formulations, as a fire retardant, antioxidant, additive for lubricants and softener of copolymers; it is also a degradation product of dimethylhydrazine, an additive to rocket fuel. Most people are exposed to NDMA via a number of diverse routes including cigarette smoke (actively or passively) and processed foods, for example smoked meat products. However, it has only come to the attention of the international water industry since it was recognised as a disinfection by-product (DBP) of chloramination or chlorination in the presence of ammonia.